KOMUNIKASI INTERPERSONAL DALAM MEMASARKAN PROGRAM CELEBRITY FITNESS KEPADA MEMBERNYA - Namira Fitria; Imelda Rifayanti (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2022)
Communication is something that cannot be separated in human life because in essence humans are social creatures who need other people. Interpersonal communication is a form of communication that occurs every day in human life. Likewise in the marketing process carried out by a marketer with his clients. In this process there is a form of communication called interpersonal communication. Celebrity fitness has several programs that must be marketed to its members through a marketing. When the marketing process requires a marketer to visit members who are exercising. Then when you are marketing that is what is called interpersonal communication. Broadly speaking, the role of marketing is to market the company's products to customers. The scope of the discussion in this journal is to find out the processes and activities in interpersonal communication between marketing and members at celebrity fitness.